Antibacterial Activity, Antioxidant Capacity and Immune Gene Modulation of Six Medicinal Plants in CHSE-214 Cells - Soo-Ji Woo; So-Sun Kim; Eun-Ji Jeon; Dong-Sung Lee; Na-Young Kim (Fishes)
This study evaluated the therapeutic potential of 70% ethanol extracts from six medicinal plants (Chenopodium album, Cassia tora, Cudrania tricuspidata, Dioscorea polystachya, Lonicera japonica, Solidago virgaurea subsp. gigantea) through their antibacterial, antioxidant, cytotoxic, and immunomodulatory activities, targeting applications in aquaculture. All extracts exhibited potent antibacterial activity (MIC ≤ 10 μg/mL) against Aeromonas spp. and Photobacterium damselae subsp. damselae, but limited efficacy against Streptococcus parauberis. C. tricuspidata (CTR) and C. tora (CTO) demonstrated superior antioxidant activity (IC50 = 1292 μg/mL and IC50 = 227 μg/mL, respectively), correlating with high polyphenol content (1498 and 1409 mg GAE/g). CTR displayed significant concentration-dependent cytotoxicity (IC50 = 904.2 μg/mL), while C. album (CA) promoted cell proliferation (132.3% viability). In LPS-stimulated CHSE-214 cells, D. polystachya (DP) induced the highest IL-8 expression (207-fold), followed by Chenopodium album (CA) (194-fold IL-8, 49-fold TNF-α) and CTR (245-fold RIPK2), activating NF-κB, MAPK, and NOD-like receptor pathways critical for teleost immunity. Lonicera japonica (LJ) suppressed TNF-α (0.4-fold) and IRF1 (0.3-fold), indicating anti-inflammatory potential, while S. virgaurea subsp. gigantea (SV) showed biphasic TNF-α modulation (79-fold at 10 μg/mL, 5-fold at 100 μg/mL). These diverse bioactivities, particularly the robust immunomodulatory effects, highlight the promise of these extracts as natural therapeutic agents for fish health management in aquaculture.